Not One World but Two. The Future in Jewish Apocalyptic Literature - Collins, John J. (Religions, 2019)
The Jewish apocalyptic literature that first appears in the Hellenistic period and continues into the Common Era developed a radically novel view of the future. As formulated in the apocalypse of 4 Ezra about the end of the first century CE, the Most High created not one world but two. This world must be utterly destroyed and replaced by a new creation. This view of the future is inherited in the New Testament, most strikingly in the Book of Revelation. It would have enormous but ambivalent implications for western history. On the one hand, it threatened to undermine the importance of working for a better life in this world. On the other hand, it offered hope to those who would otherwise have no hope at all.